Pembatasan Masa Jabatan Ketua Umum Parpol Dalam Perspektif Demokrasi - Baharuddin Riqiey; Adella Anggia Pramesti; Alif Cahya Sakti (Jurnal Mengkaji Indonesia, 2022)
Abstract: This research aims to review and know the authority of the government to regulate the term of the chairman of a political party and review and analyze the urgency of limiting the term of the chairman of a political party. Purpose: The problem that occurs in political parties in Indonesia today is that there is no regulation of the term of the chairman of the political party it causes the creation of a healthy democracy, the emergence of dynastic politics, and the lack of regeneration in the body of political parties. Design/Methodology/Approach: This research is legal research with a normative legal research type. Which approach is used is an approach with laws and regulations and other regulations. The legal materials used are primary and secondary legal materials. Findings: The results of the study showed that the government is authorized to regulate the term of office of the party's general chairman, through the revision of the Political Party Law related to the regulation of the term of the chairman of the political party. Originality/value: there is no article that discusses the limitation of the term of office of the chairman of a political party, so this is an article that discusses the urgency of limiting the term of office of the chairman of a political party.